Pengaruh Koneksi Politik terhadap Penghindaran Pajak - Nabila Khoirunnisa Asadanie; Lintang Venusita (Universitas PGRI Madiun, 2020)
This study aims to examine the effect of political connection on tax avoidance. The sample in this study were manufacture companies from the BEI for the periode 2015-2017. The sample were selected using purposive sampling technique and obtained a sample of 55 companies. The analysis technique used in this study is multiple linear regressions analysis using IBM SPSS Statistic program 23. The result of the study show that political connection has a negative effect on tax avoidance.Keywords: political connection, tax avoidance.